"BIBLIOMETRIC MAPPING" OF ISLAMIC FINTECH AND FINANCIAL INCLUSION IN DEVELOPING COUNTRIES - Endah Robiatul Adawiyah; Eti Jumiati; Hawwa Abdul Mokti; Mahmud Syukri; Dhiwa Lulu Qurotulaini (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the development of research on Islamic fintech and financial inclusion in developing countries through bibliometric and network analysis approaches. The study also aims to identify publication trends, patterns of collaboration between researchers and countries, as well as the main themes that are developing in the scientific literature related to Islamic fintech. The research uses a bibliometric method with the data source coming from the Scopus database. Data collection was carried out in January 2024 using keywords related to "Islamic fintech" and "financial inclusion" in the TITLE-ABS-KEY field. The document selection process was carried out using the PRISMA approach with the criteria for English-language journal articles for the 2018–2024 period. From the initial 313 documents, 150 articles were obtained that met the criteria for analysis using the VOSviewer and Biblioshiny (R-Studio) software. The results show that publications on Islamic fintech and financial inclusion have increased significantly during the period 2018–2024, with the peak of publication occurring in 2024. Malaysia and Indonesia are the countries with the most dominant research contributions and collaborations. Keyword analysis shows that the main themes of the research include Islamic fintech, financial technology, financial inclusion, Islamic banking, P2P lending, digital payment, financial literacy, and blockchain. The findings also show that Islamic fintech plays an important role in supporting financial inclusion through sharia-based financial services that are more accessible, especially for people who have not been reached by conventional banking services. The implications of this study show that Islamic fintech has great potential as an instrument to strengthen financial inclusion in developing countries. Therefore, regulatory support, increased Islamic financial literacy, and strengthening collaboration between countries and institutions are needed to encourage the development of a more inclusive and sustainable Islamic fintech ecosystem. This research provides an important foundation for policy makers, industry players, and academics in designing a more inclusive Islamic fintech development strategy.